SURGICAL MANAGEMENT & CLINICAL OUTCOME OF OCCIPITAL ENCEPHALOCOELE - Najm us saqib; Sharif Alqadhi; Usman Ahmed Khan (Journal of University Medical & Dental College, 2017)
ABSTRACT: INTRODUCTION: Encephalocele is a protrusion of the endocranial content through a bone defect & which is caused by an embryonic development abnormality.2,3 If the herniation of meninges and cerebrospinal fluid (CSF) it is termed a meningocele, when both neural elements and meninges herniated through the opening it is termed encephalomeningocele. Hydroencephalomeningocele is term used to describe herniation of the brain tissue, ventricles and meninges through the cranium. AIMS OF STUDY: To determine the surgical outcomes of Occipital encephalocele in our setting, to present our experience of 18 patients with managed surgically and to compare these with similar results of standard international studies. METHODS: Cross sectional Study. Starting from september 2011 to september 2015. This is a study of 18 operated cases of Posterior encephaloceles (occipital, parietal) presenting at Neonatology, OPD department neurosurgery and A&E department of Khoula hospital ministry of health Muscat, Sultanate of Oman. Each patient with suspected encephalocele was evaluated by the neurosurgeon, All the data recorded by age, sex and size of encephalocele , associated congenital cranial and systemic abnormalities, investigations like CT & MRI, operative and postoperative results. The six months outcome at discharge from the hospital was assessed at the time of OPD follow up. VP shunts used where associated hydrocephalus was present. The data was analyzed with SPSS. Relevant descriptive statistics presented. All data collected on a performed Performa. RESULTS: In this study we have divided our results into three categories according to patient’s surgical wound healing, growth and mental functions assessment, head circumference, symptoms of meningitis, neurological deficit and evidence of recurrence encephalocele (Repeat CT scan brain plain 6 Moths after surgery). CONCLUSION: The frequency rate of Posterior encephaloceles is significant in Oman. The neurological prognosis in children depends on the amount of herniated neural tissue & the presence of associated malformations. The absence of brain tissue in the sac was the single most important favourable prognostic feature for survival while the presence of hydrocephalus may an adverse factor.